Structural Analysis on Edgar Allan Poe’s Short Story Murders in the Rue Morgue - Rahayuningsih, Mahsunah Etik (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2019)
This thesis presents an analysis on Edgar Allan Poe’s short story entitled Murder in the Rue Morgue. The purposes of this thesis are, first, to know the intrinsic elements of Murder in the Rue Morgue such as setting, character, plot and conflict, and theme. Second, to find out the relationship among the intrinsic elements of the short story. The methods used in this thesis were library research method and structural approach method. The library research method was applied to get information to support the ideas of this thesis, in this research using Edgar Allan Poe’s Short Story. Meanwhile, the structural approach method was used to analyze the intrinsic elements and how they are related one to another. The result of the analysis shows how the intrinsic elements especially setting, character, plot and conflict and theme are described in Murder in the Rue Morgue. From the analysis above we know, that Murder in the Rue Morgue tells about thriller and massacre happens in Rue Morgue, fourth floor apartment. The writer makes conclusion that the theme is “analytic mind is useless without assistance and cooperation” The theme is based on the fact that the main character named Dupin has analytic mind, with his analytic mind, he can solve every case happens around him. When there is murder case in Rue Morgue, the cooperation and assistance are formed then the truth is revealed, and the murderer is Ourang-outang. Penelitian ini menyajikan analisis tentang cerita pendek Edgar Allan Poe berjudul Murder in Rue Morgue. Tujuan dari tesis ini adalah, pertama, untuk mengetahui unsur-unsur intrinsik Pembunuhan di Rue Morgue seperti seting, karakter, plot dan konflik, dan tema. Kedua, untuk mengetahui hubungan unsur intrinsik dari cerpen. Metode yang digunakan dalam tesis ini adalah metode penelitian kepustakaan dan metode pendekatan struktural. Metode penelitian perpustakaan diterapkan untuk mendapatkan informasi untuk mendukung ide-ide tesis ini, dalam penelitian ini menggunakan Cerpen Edgar Allan Poe. Sementara itu, metode pendekatan struktural digunakan untuk menganalisis elemen intrinsik dan bagaimana mereka terkait satu sama lain. Hasil analisis menunjukkan bagaimana elemen intrinsik terutama pengaturan, karakter, plot dan konflik dan tema dijelaskan dalam Murder in Rue Morgue. Dari analisis di atas kita tahu, bahwa Pembunuhan di Rue Morgue bercerita tentang film pembunuhan dan pembantaian yang terjadi di Rue Morgue, di depan apartemen. Penulis membuat kesimpulan bahwa tema adalah "pikiran analitik tidak berguna tanpa bantuan dan kerjasama" Tema ini didasarkan pada kenyataan bahwa karakter utama bernama Dupin memiliki pikiran analitik, dengan pikiran analitiknya, ia dapat menyelesaikan setiap kasus yang terjadi di sekitarnya. Ketika ada kasus pembunuhan di Rue Morgue, kerja sama dan bantuan terbentuk maka kebenaran terungkap, bahwa pembunuhnya adalah Ourang-outang.